The joint regulation of bank liquidity and bank capital - DeYoung, Robert; Distinguin, Isabelle; Tarazi, Amine (Journal of Financial Intermediation, 2018)
We study the liquidity behavior of commercial banks in response to negative capital shocks. Using pre-Basel III data, U.S. banks with assets less than $1 billion treated (unregulated) liquidity and (regulated) capital as substitutes. Following exogenous shocks to their regulatory capital ratios, these banks shifted away from loans, loan commitments, and dividend payouts, actions that both repaired their capital ratios and enhanced their liquidity positions. We find little similar behavior at larger banks. We conclude that a minimum capital constraint naturally mitigates liquidity risk at community banks, justifying the exemption of these banks from the Basel III liquidity standards.